Introducing the special issue on 'Comparative studies in early childhood education: past, present and future'. Issue 3 (3rd July 2022) - Sousa, Diana; Moss, Peter
ABSTRACT: In recent years, Early Childhood Education (ECE) has emerged as a policy priority for many governments and international organisations. Yet while there has been much research about ECE, and despite some notable exceptions, comparative studies have figured less in ECE than in other sectors of education. This paper introduces the special issue on 'comparative studies in early childhood education'. It provides the rationale for this issue alongside a brief historical overview of the relationship between ECE and comparative education, explaining how the embodiment of diverse forms of comparative enquiry can reveal interplays between policy, politics and practice in the past, present, and future comparative studies of ECE. It concludes by introducing the contrast between comparative education as a 'science of solutions' and as a 'science of difference', concepts that frame the special issue.